Technological progress and its impact on the labor market - Myrzalieva, G.A.; Issakhmetova, A.N.; Abilkassym, A.B.; Turakulova, L.R.; Mukhamedkhanova, A.B. (BUKETOV BUSINESS REVIEW, 2024)
Object: The purpose of this research is to examine how advancements in technology influence the job market, highlight key trends and effects, and formulate suggestions for both employees and employers to adjust to the shifts brought about by emerging technologies. Methods: The research methodology includes methods of systematic and institutional analysis. To carry out the study, a set of data was used that contained information about investments in new technologies, the unemployment rate and other variables related to this group. To determine the existence of a relationship between investments in digitaliza tion and the unemployment rate correlation and regression analysis were used. Results: Technological progress requires new skills and knowledge from employees. The demand for specialists in IT, Data Analysis and digital marketing is growing, and traditional professions are losing their relevance. Thus, final research can be an important tool for organizations that seek not only technological renewal, but also the creation of fair and productive jobs. Conclusions: Technological advancement profoundly influences the job market, generating both fresh opportuni ties and obstacles. To maintain competitiveness, both employers and employees need to adjust to these changes. It is essential to implement strategies that enhance workers’ skills, facilitate their adjustment to evolving circumstances, and establish retraining initiatives for individuals who have been displaced by automation.